A gramaticalização do verbo ir e a variação de formas para expressar o futuro do presente : uma fotografia capixaba - Bragança, Marcela Langa Lacerda (2008)
This research verifies the process of gramaticalization of the verb TO GO, that has assumed the function of auxiliary in periphrastic constructions to express time. For that, the variation between the synthetic and periphrastic forms with TO GO to express future is investigated. As a hypothesis, we assume that the periphrastic form already reaches all the text genres of the two modalities of the language, once it has already been specialized to codify time. Two genres are examined, taking them as prototypical of the verbal/written continuum: interviews with university informers and editorials. Relying on a Functionalist theoretical orientation, in a more general picture, language is conceived as flexible to the use, liable to receiving cognitive, social and also individual influences, even though it has in it forces that act to regulate its structure. Following some research projects that have seemed to be fruitful, the functionalist model will be in dialogue with another model that deals with the structuralized heterogeneity of the language and its processes of change: the Variation Theory. In a more specific picture, this research relies on the Gramaticalization Theory. The data collected from the selected genres will be analysed with the help of the computacional program GOLDVARB and, after that, interpreted in the light of the linguistic theories that form the basis of this research.